Most new HIV infections, vertical transmissions and AIDS-related deaths occur in lower-prevalence countries - Joe Kempton; Andrew Hill; Jacob A. Levi; Katherine Heath; Anton Pozniak (Elsevier, 2019)
Objectives: The Joint United Nations Programme on HIV/AIDS (UNAIDS) targets aim to reduce new HIV infections below 500,000 per year by 2020. Despite targeted prevention programmes, total new infections remained in 2016 and 2017 at 1,800,000 cases. We have aimed to analyse data from 2017 and to compare HIV incidence, AIDS-related deaths and provision of antiretroviral therapy (ART) to adults, pregnant women and children living with HIV in lower- and higher-prevalence countries. Vertical or mother-to-child transmission (MTCT) and early infant diagnosis (EID) rates were also investigated. Methods: UNAIDSinfo data use the Spectrum model to represent country-level HIV data. Countries with epidemics over 40,000 HIV cases were separated into higher prevalence (≥4.5%) and lower prevalence (<4.5%). Least squares linear regression, weighted by epidemic size and controlled for gross domestic product/capita, was used to compare HIV prevalence with estimated ART coverage in adults (≥15 years), children (0-14 years), pregnant women, and EID rates and MTCT rates. Data were then compared between higher- and lower-prevalence groups, including numbers of new HIV infections and AIDS-related deaths. Results: Data were available for 56 countries. Twelve higher-prevalence countries accounted for 16.7 million and 44 lower-prevalence ones for 15.1 million people living with HIV, altogether making up 87.5% of the global estimate. Lower-prevalence countries had less ART coverage for adults, pregnant women and children, lower EID rates and higher AIDS-related death levels. There were more new HIV infections in adults and children in lower- than higher-prevalence countries. Conclusions: Most new HIV infections, MTCTs and AIDS-related deaths occurred in countries with an HIV prevalence rate below 4.5%. Many of these countries are not targeted by access programmes, such as the President' Emergency Plan for AIDS Relief. More intensive programmes of diagnosis and treatment are needed in these countries in the effort to reduce global new HIV infections below 500,000 per year by 2020.